Letterer-Siwe's disease - Bilir, Şule (The Turkish Journal of Pediatrics, 1971)
Four cases of Letterer-Siwe's disease are presented and clinical and pathological results are discussed together with a brief review of the literature. The significance of the effects of malnutrition and secondary infections on the prognosis of this disease is emphasized.